2022
DOI: 10.3389/fonc.2022.884369
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles and Hepatocellular Carcinoma: Opportunities and Challenges

Abstract: The incidence of hepatocellular carcinoma (HCC) is increasing worldwide. Extracellular vesicles (EVs) contain sufficient bioactive substances and are carriers of intercellular information exchange, as well as delivery vehicles for nucleic acids, proteins and drugs. Although EVs show great potential for the treatment of HCC and their role in HCC progression has been extensively studied, there are still many challenges such as time-consuming extraction, difficult storage, easy contamination, and low drug loading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 298 publications
0
14
0
Order By: Relevance
“…It is interesting to note that HCC-derived exosomes can regulate immune cells during the progression of tumors 8,9 . Another study has verified that HCC cells–secreted EVs produce direct immune effects to stimulate target cells, contributing to the invasion of HCC 10 . Moreover, bioinformatics analysis in the current study revealed that lysyl oxidase like-4 (LOXL4) was differentially expressed in HCC.…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…It is interesting to note that HCC-derived exosomes can regulate immune cells during the progression of tumors 8,9 . Another study has verified that HCC cells–secreted EVs produce direct immune effects to stimulate target cells, contributing to the invasion of HCC 10 . Moreover, bioinformatics analysis in the current study revealed that lysyl oxidase like-4 (LOXL4) was differentially expressed in HCC.…”
mentioning
confidence: 54%
“…8,9 Another study has verified that HCC cellssecreted EVs produce direct immune effects to stimulate target cells, contributing to the invasion of HCC. 10 Moreover, bioinformatics analysis in the current study revealed that lysyl oxidase like-4 (LOXL4) was differentially expressed in HCC. Emerging evidence has proved the roles of LOXL4 in tumor cell growth and metastasis, including HCC.…”
mentioning
confidence: 71%
“…Recently, surface markers of EVs have gained attention since they indicated presence of HCC and cholangiocarcinoma with increased levels of CD147 and CD133 [13]. Additionally, EVs transfer proteins and different types of RNAs, including miRNAs, from highly malignant cells to surrounding cells, promoting HCC migratory and metastatic capacities [14]. This is of particular interest because tumor invasion lead to early recurrence of HCC after resection, resulting in high recurrence rates [15].…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] Secretion of exosomes is a pivotal way for BMSC to exert effects on cancer progerssion. 17,18 Accumulating evidence showed that exosomes released from BMSCs regulate tumor progression by packaging some specific miRNAs. [19][20][21] But limited studies focused on the effect of BMSC-derived exosomes exerting on HCC metastasis via transmitting specific miRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…BMSCs are multipotent cells which function in different human pathological processes, including cancer development 14–16 . Secretion of exosomes is a pivotal way for BMSC to exert effects on cancer progerssion 17,18 . Accumulating evidence showed that exosomes released from BMSCs regulate tumor progression by packaging some specific miRNAs 19–21 .…”
Section: Introductionmentioning
confidence: 99%